Whole-tumour histogram analysis of pharmacokinetic parameters from dynamic contrast-enhanced MRI in resectable oesophageal squamous cell carcinoma can predict T-stage and regional lymph node metastasis. Issue 112 (March 2019) - Chen, Yan-li; Li, Rui; Chen, Tian-wu; Ou, Jing; Zhang, Xiao-ming; Chen, Fan; Wu, Lan; Jiang, Yu; Laws, Maxwell; Shah, Kamran; Joseph, Bobby; Hu, Jiani
Highlights: Histogram metrics of whole-tumour pharmacokinetic parameters helps predict T-stage of oesophageal squamous cell carcinoma. Histogram metrics of pharmacokinetic parameters helps predict lymph node metastasis of oesophageal squamous cell carcinoma. Entropy of Ve better identifies T-stage and standard deviation of Kep determines lymph node metastasis. Abstract: Objective: To identify whether whole-tumour histogram analysis of pharmacokinetic parameters from dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) could predict T-stage and regional lymph node metastasis (LNM) of resectable oesophageal squamous cell carcinoma (SCC). Materials and methods: Forty-two consecutive patients with confirmed oesophageal SCC underwent thoracic DCE-MRI. Histogram metrics (median, mean, standard deviation [SD], skewness, kurtosis and entropy) of whole-tumour pharmacokinetic parameters including endothelial transfer constant (K trans ), reflux rate (Kep ) and fractional extravascular extracellular space volume (Ve ) were generated by the Omni-Kinetics software. Histogram datasets were interpreted using the Mann-Whitney U test and receiver operating characteristic (ROC) statistical analyses. Results: The Mann-Whitney U tests revealed that the median, mean and SD of K trans, the SD and entropy of Kep, and the median, mean and entropy of Ve of T1-2 stage oesophageal SCC were lower when compared with T3 stage (all Ps < 0.05); and the ROC analysis showed that the entropy of Ve could reliably distinguish T1-2 stage from T3 stage with an area under ROC (AUC) of 0.773. The Mann-Whitney U tests illustrated that the entropy of K trans, and the median, mean, SD and entropy of Kep were higher while the skewness of Kep was lower in tumours with LNM than without LNM (all Ps < 0.05); and the ROC analysis demonstrated that the SD of Kep could best identify tumours with LNM with an AUC of 0.702. Conclusion: Whole-tumour histogram analysis of pharmacokinetic parameters of oesophageal SCC on DCE-MRI could be used to predict T-stage and regional LNM.